Analisis Efektivitas dan Kontribusi Komponen Pajak PKB. BBNKB dan PBBKB Terhadap Pendapatan Asli Daerah Provinsi Jambi Periode Tahun 2016 - 2018 - Fathiyah Fathiyah; Mufidah Mufidah; Masnun Masnun (Universitas Batanghari, 2019)
This research aims to analyze the effectiveness of revenue per type of local tax and its contribution to the region own source revenue (PAD) Jambi Province Year 2016 – 2018. The data used in this research is the secondary data taken from the budget Realization report on the financial statement of the provincial government of Jambi province year 2016 – 2018, then the data is processed using the effectiveness percentage formula Per type of tax and contribution percentage per tax type against PAD Jambi province. The results of this study concluded that the effectiveness of the admission per type of regional tax (PKB, BBNKB and PBBKB) of the provincial government of Jambi overall entered in the criteria is very effective, although in the last two years for tax BBNKB and PBBKB less Effective but every year continues to increase improvement and in the third year reaches the magnitude of the target that is a trailer set or > 100% until the third year of 2018 entered in the criteria is very effective. As for the percentage of contributions per tax type (PKB, BBNKB, and PBBKB) to PAD Jambi Province in the last three years the achievement is below 60% with ineffective criteria. This indicates that the contribution per tax type is very small to the PAD and automatically the number of PAD that are absorbed or received by the provincial government of Jambi in 2016 – 2018 very small, So that dependence of Jambi provincial government to transfer funds from the central government to finance the development is still very large.